This preview shows pages 1–8. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: ± λ λ + x ² α . [6] S T ( x ) = 1F T ( x ) = 1Z x f T ( s ) ds = 1Z x αλ α ( λ + s ) α +1 ds = λ α ( λ + x ) α 5 (b) Derive an expression for μ x . [5] μ x = f T ( x ) S T ( x ) = α λ + x Note that f T ( x ) and S T ( x ) are given in the question. 6 (c) Derive an expression for S T x ( t ). [5] S T x ( t ) = S T ( x + t ) S T ( x ) = ± λ λ + x + t ² α ± λ λ + x ² α = ³ λ + x λ + x + t ´ α . 7 (d) Using (b) and (c), or otherwise, ﬁnd an expression for f T x ( t ). [5] f T x ( t ) = S T x ( t ) μ x + t = ± λ + x λ + x + t ² α α λ + x + t . 8...
View
Full
Document
This note was uploaded on 03/20/2011 for the course ACTSC 232 taught by Professor Matthewtill during the Summer '08 term at Waterloo.
 Summer '08
 MATTHEWTILL

Click to edit the document details